Potentiating bioactivity of BMP‐2 by polyelectrolyte complexation with sulfonated polyrotaxanes to induce rapid bone regeneration in a mouse calvarial defect. Issue 5 (24th February 2017) - Terauchi, Masahiko; Inada, Takasuke; Kanemaru, Tomoki; Ikeda, Go; Tonegawa, Asato; Nishida, Kei; Arisaka, Yoshinori; Tamura, Atsushi; Yamaguchi, Satoshi; Yui, Nobuhiko
Abstract: Bone reconstruction is a challenging issue in the regeneration of surgically removed bone and disease‐related bone defects. Although bone morphogenetic protein‐2 (BMP‐2) has received considerable attention as a bone regeneration inducer, a high dose of BMP‐2 is typically required due to its short life‐time under in vivo conditions. We have proposed a method to enhance the osteogenetic differentiation ability of BMP‐2 in vitro that is based on supramolecular polyelectrolyte complexation with sulfonated polyrotaxanes (PRXs) consisting of sulfopropyl ether (SPE)‐modified α‐cyclodextrins threaded along a poly(ethylene glycol) chain capped with terminal bulky stopper molecules. In this study, we evaluated the in vivo bone regeneration ability of the SPE‐PRX/BMP‐2 complexes in a mouse calvarial defect model in comparison to free BMP‐2 and heparin/BMP‐2 complexes. The regenerated bone area was determined by X‐ray computed microtomography, and the mice implanted with sulfonated PRX/BMP‐2 complexes exhibited rapid and significant bone regeneration compared to those implanted with free BMP‐2 and heparin/BMP‐2 complexes. We concluded that the sulfonated PRX/BMP‐2 complexes are a promising candidate for clinical bone regeneration. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1355–1363, 2017.